Unraveling Green Consumer Behaviour: A Systematic Literature Review - Bansah, Pearl Fafa; Gaffar, Vanessa; Disman, Disman; Yeliawati, Ayu Krishna (Universitas Airlangga, 2024)
Background: Environmental concerns are increasingly influencing consumer decision-making, and green consumer behaviour has garnered attention in marketing and sustainability. Businesses, governments and researchers must understand green consumer behaviour in order to understand sustainable consumption motives, attitudes, and decisions. Objective: The objectives of this review are to analyse and synthesise how researchers characterise and define green consumer behaviour, examine and evaluate the various research methods used to investigate it, and identify and discuss emerging trends and patterns in green consumer behaviour research. Methods: This review followed the PRISMA standards for systematic literature reviews. A thorough screening procedure was used to select 64 papers from 1633. The EBSCOhost Business Source Ultimate, Science Direct, and Emerald were used. Only English-language research papers published between 2005 and 2023 were included. Articles were found using the